2017
DOI: 10.1001/jama.2017.13883
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Use of Non–Vitamin K Oral Anticoagulants With and Without Concurrent Medications and Risk of Major Bleeding in Nonvalvular Atrial Fibrillation

Abstract: Among patients taking NOACs for nonvalvular atrial fibrillation, concurrent use of amiodarone, fluconazole, rifampin, and phenytoin compared with the use of NOACs alone, was associated with increased risk of major bleeding. Physicians prescribing NOAC medications should consider the potential risks associated with concomitant use of other drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
364
0
8

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(391 citation statements)
references
References 46 publications
5
364
0
8
Order By: Relevance
“…However, apixaban was still more effective as compared to warfarin, while in terms of major bleeding, its benefits decreased with increasing number of concomitant drugs. A study in Taiwan found an increased bleeding risk in patients with nonvalvular atrial fibrillation (NVAF) taking a DOAC along with amiodarone, fluconazole, rifampin, or phenytoin (medications with a common metabolic pathway) compared to a DOAC alone …”
Section: Introductionmentioning
confidence: 99%
“…However, apixaban was still more effective as compared to warfarin, while in terms of major bleeding, its benefits decreased with increasing number of concomitant drugs. A study in Taiwan found an increased bleeding risk in patients with nonvalvular atrial fibrillation (NVAF) taking a DOAC along with amiodarone, fluconazole, rifampin, or phenytoin (medications with a common metabolic pathway) compared to a DOAC alone …”
Section: Introductionmentioning
confidence: 99%
“…,19 A nationwide observational cohort study in Taiwan demonstrated that use of atorvastatin was associated with a significantly lower incidence rate for major bleeding in patients with NVAF who were also taking dabigatran, rivaroxaban, or apixaban 20. These patterns TA B L E 1 Baseline characteristics and cumulative bleeding events of statin users and non-users…”
mentioning
confidence: 98%
“…Recently, an interesting and complex study was published on JAMA (Chang et al, ) about the bleeding risk associated with the use DOACs and 12 concurrent medications commonly prescribed that sharing common metabolic pathways with DOACs (e.g. P‐glycoprotein competitors and CYP3A4 inhibitors).…”
mentioning
confidence: 99%